Sorption of Perfluorooctane Sulfonic Acid Including Its Isomers to Soils: Effects of pH, Natural Organic Matter and Na2SO4 - Uwayezu, Jean-Noel; Yeung, Leo W. Y.; Bäckström, Mattias (Frontiers in Environmental Chemistry, 2022)
Perfluorooctane sulfonic acid (PFOS) has been produced in large quantities for the use in various applications. As a consequence, PFOS is ubiquitous in the environment. Managing transportation of PFOS requires a clear understanding of PFOS mobilization in soils and their interactions with different soil components. The current study investigated a pH-dependent sorption of PFOS isomers onto soil and the effect of dissolved humic substances or Na2SO4. Sorption experiments of PFOS isomers was conducted on top and subsoils to assess their capacity to retain PFOS. Topsoil and subsoil samples were sampled from two area in Kvarntorp in Kumla, Sweden. Sorption experiments were performed by shaking a mixture of soil and soil solutions spiked with PFOS isomers. One way ANOVA showed that linear PFOS (L-PFOS) and branched PFOS (Br-PFOS) isomers showed different sorption behavior onto soils. Calculated logarithmic partition coefficients revealed that L-PFOS is readily sorbed onto soils sampled at area (1) at very low pH (< 4.5) whereas it was the least sorbed onto soils collected at area (2) under the studied pH range. Electrostatic interactions governed the sorption of PFOS isomers during acidic conditions whereas other mechanism controlled the sorption during neutral to alkaline conditions. The presence of humic acid enhanced the sorption of all PFOS isomers whereas fulvic acid inhibited their sorption onto soil. Sorption results revealed the topsoil had a high capacity to sorb all PFOS isomers compared to the subsoil at the same area. For soils collected from an area that was covered by young oak trees, a high sorption on the top soil was attributed to a high organic content (measured as loss on ignition (LOI)) and cation exchange capacity (CEC). However, there was no correlation between sorption capacity and TOC or CEC content for soil collected from another area covered by spruce forest. This suggested that the sorption on latter soils was controlled by other physicochemical properties.